Status of Information and Communication Technology (ICT) in Health Profession Education in Kenya - A. McNulty, John; Otieno, Antony; Gachoka, Steven; Hillary, Edalia; Juma, Faith; Maingi, Martin; Mugire, Saidi; Mwangi, Samuel; Yallah, Collins; B. Harrison, Kathleen (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Because ICT is an integral component of health care and education, we evaluated the status of ICT among health profession students (n=310) at 5 universities in Kenya. Most students owned a computer (73%) or smart phone (60%). Ownership of ICT devices was significantly associated with familiarity of technology and Internet accessibility. Most students (54%) agreed that computer instruction (CAI) was available in their curriculum, but only 39% used it routinely. Males were more familiar with ICT than females, which was the only important gender difference. These data and the variability in responses across universities provide important information for the continued development of policies to promote ICT in health education.